The effective usage of corpora in legalese studies (on the example of the fiducie) - Gvelesiani, Irina (Comparative Legilinguistics, 2024)
If we consider corpus linguistics as the study of a language through its samples, we should give credit to its contribution to the advancement of various sub-fields of linguistics: lexicography, translation studies, applied linguistics, diachronic studies and contrastive linguistics. The latter can be regarded as a special case of a linguistic typology that is distinguished from other types of typological approaches by a small sample size and a high degree of granularity (Gast 2011: 2-3). Nowadays, corpus-based contrastive studies can be treated as a growing research area that focuses on two or more languages. The present paper makes an attempt to discuss the usefulness of the specialized combined parallel-comparable corpus while dealing with legalese. The effectiveness is presented on the example of the legal institution fiducie. The methodology of research comprises the comparative analysis as well as the corpus-based analysis of the terms related to the fiducie-s presented in three varieties of French: France’s, Canadian and Luxembourgish. The carried out research reveals the juridical-semantic differences and the problematics of the verbal realization of the concepts related to three fiducie-s. These hinder a proper interpretation and complicate the process of translation. The major solution is found through the specification of meaning by renaming.